HUBUNGAN ANTARA KREATIVITAS MENGGAMBAR MELALUI FINGER PAINTING DENGAN KEMAMPUAN MOTORIK HALUS ANAK USIA DINI (Penelitian di Kelompok A RA Az-Zahra Bandung) - Daulay, Fauziah Rahmadani; Kurnia, Aam; Nursihah, Arif (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
This research was motivated by the gap between high creativity in drawing through finger painting with low fine motor skills in early childhood. It can be seen that the creativity of drawing through finger painting basically already has the skills in drawing through fingers well. But in contrast to fine motor skills, children still have difficulty in developing fine motor skills when carrying out finger painting activities. This study aims to find out: (1) Creativity in drawing through finger painting in Group A of RA Az-Zahra Bandung Regency, (2) Fine motor skills of early childhood in Group A of RA Az-Zahra Bandung Regency and (3) The relationship between creativity in drawing through finger painting with fine motor skills of early childhood in Group A of RA Az-Zahra Bandung Regency. The research method used by researchers is quantitative research and the approach used is product moment correlation. The subjects of the study were group A RA Az-Zahra with a total of 18 children. Observation, interview and documentation data collection techniques. The data analysis techniques carried out are validity tests, reliability tests, normality tests, linearity tests, and hypothesis tests. Based on the results of the study that creativity in drawing through finger painting in Group A RA Az-Zahra Bandung Regency, has an average value of 77, is in the interval 70-79 which has good criteria. Early childhood fine motor skills in Group A RA Az-Zahra, Bandung Regency, have an average score of 74 being in the interval 70-79 which has good criteria. The results of the product moment correlation analysis, which obtained a correlation result of 0.593, at a significant level of 5% obtained a result of 0.593>0.468, the calculated r value was in the interval 0.400-0.599 the level of the relationship (moderate). Thus, it can be concluded that there is a (moderate) relationship between the creativity of drawing through finger painting with the fine motor skills of early childhood in Group A RA Az-Zahra, Bandung Regency.